Comparative Analysis of Local Government Financial Performance Before and During Covid-19 Pandemic - Rafael, Sarinah; Istianah, Iis (Badan Pemeriksa Keuangan Republik Indonesia, 2022)
The COVID-19 pandemic has had a compelling impact on various sectors in Indonesia, including the national economy. This study aims to examine differences in regional financial performance before the pandemic (2019) and during the pandemic (2020) and to examine the effect of the ranking and status of local government administration published by the Ministry of Home Affairs on regional financial performance in the period before the pandemic (2019) and during the pandemic (2020). Paired sample t-test and regression analysis were used to test the hypotheses on the financial performance of 118 local governments consisting of 16 provincial governments, 48 ​​district governments, and 54 city governments. The regional financial independence ratio (RKKD), the effectiveness and efficiency ratio of PAD, the activity ratio, and the growth ratio are financial performance indicators tested in this research. The research's results show the differences between before and during the COVID-19 pandemic in regional financial performance in the PAD effectiveness ratio, capital expenditure activity ratio, and growth ratio. However, there is no difference in regional financial performance before and during the COVID-19 pandemic as measured by the regional financial independence ratio, efficiency ratio, and operating expenditure activity ratio. The results also show that the ranking and status of local government administration have no effect on regional financial performance before and during the COVID-19 pandemic.